High Power Conversion Efficiency of 13.61% for 1 cm2 Flexible Polymer Solar Cells Based on Patternable and Mass‐Producible Gravure‐Printed Silver Nanowire Electrodes. (15th October 2020) - Wang, Zhenguo; Han, Yunfei; Yan, Lingpeng; Gong, Chao; Kang, Jiachen; Zhang, Hao; Sun, Xue; Zhang, Lianping; Lin, Jian; Luo, Qun; Ma, Chang‐Qi
Abstract: With the aim of developing high‐performance flexible polymer solar cells, the preparation of flexible transparent electrodes (FTEs) via a high‐throughput gravure printing process is reported. By varying the blend ratio of the mixture solvent and the concentration of the silver nanowire (AgNW) inks, the surface tension, volatilization rate, and viscosity of the AgNW ink can be tuned to meet the requirements of gravure printing process. Following this method, uniformly printed AgNW films are prepared. Highly conductive FTEs with a sheet resistance of 10.8 Ω sq −1 and a high transparency of 95.4% (excluded substrate) are achieved, which are comparable to those of indium tin oxide electrode. In comparison with the spin‐coating process, the gravure printing process exhibits advantages of the ease of large‐area fabrication and improved uniformity, which are attributed to better ink droplet distribution over the substrate. 0.04 cm 2 polymer solar cells based on gravure‐printed AgNW electrodes with PM6:Y6 as the photoactive layer show the highest power conversion efficiency (PCE) of 15.28% with an average PCE of 14.75 ± 0.35%. Owing to the good uniformity of the gravure‐printed AgNW electrode, the highest PCE of 13.61% is achieved for 1 cm 2 polymer solar cells based on the gravure‐printed FTEs. Abstract : Large‐area prepatterned silver nanowire electrodes are prepared via gravure printing, which show high uniformity and balanced conductivity (10.8 Ω sq −1 ) and transparency (95.4%). High power conversion efficiencies of 15.28% and 13.61% are achieved for 0.04 and 1 cm 2 cells, respectively.